Extensive metazoan reefs from the Ediacaran Nama Group, Namibia: the rise of benthic suspension feeding. Issue 2 (30th December 2014) - Wood, R.; Curtis, A.
Abstract We describe new, ecologically complex reef types from the Ediacaran Nama Group, Namibia, dated at ~548 million years ago (Ma), where the earliest known skeletal metazoans, Cloudina riemkeae and Namacalathus, formed extensive reefs up to 20 m in height and width. C. riemkeae formed densely aggregating assemblages associated with microbialite and thrombolite, each from 30 to 100 mm high, which successively colonised former generations to create stacked laminar or columnar reef frameworks. C. riemkeae individuals show budding, multiple, radiating attachment sites and cementation between individuals. Isolated Namacalathus either intergrew with C. riemkeae or formed dense, monospecific aggregations succeeding C. riemkeae frameworks, providing a potential example of environmentally mediated ecological succession. Cloudina and Namacalathus also grow cryptically, either as pendent aggregations from laminar crypt ceilings in microbial framework reefs or as clusters associated with thrombolite attached to neptunian dyke walls. These reefs are notable for their size, exceeding that of the succeeding Lower Cambrian archaeocyath–microbial communities. The repeated colonisation shown by C. riemkeae of former assemblages implies philopatric larval aggregation to colonise limited favourable substrates. As such, not only were skeletal metazoans more important contributors to reef building in the Ediacaran, but there were also more variable reef types with more complex ecologies, than previously thought. Such an abundance of inferred suspension feeders with biomineralised skeletons indicates the efficient exploitation of new resources, more active carbon removal with a strengthened energy flow between planktic and benthic realms, and the rise of biological control over benthic carbonate production. These mark the prelude to the Cambrian Explosion and the modernisation of the global carbon cycle.